A Trichophyton mentagrophytes Dermatomycosis in Two Donkeys in Tanzania: Clinical, Pathological and Chemotherapeutic Findings - Matovelo, J.A.; Cooper, J.E.; Mellau, L.S.B.; Mtambo, M.M.A. (Tanzania Veterinary Journal, 2000)
Two sick donkeys (Equus asinus) bearing wide spread skin lesions characterized by extensive patches of alopecia exhibiting asbestos-like flakes of scales and multiple pruritic scabs were presented for investigation and management. Dermatophytosis (ringworm) was diagnosed in both donkeys. One animal showed a rapid and dramatic response to treatment with oral Griseofulvin. The other donkey responded poorly to treatment probably due to complicating secondary bacterial infections and was therefore euthanised. Following the euthanasia, tissue samples from affected sites on the skin were collected for histopathological and microbiological investigation. The diagnosis of ringworm was based on the clinical signs, post-mortem findings, the demonstration of fungal hyphae in histological sections and the cultural isolation of Trichophyton mentagrophytes from skin scrapings